2009
DOI: 10.1002/ab.20309
|View full text |Cite
|
Sign up to set email alerts
|

Rough‐and‐tumble play and the regulation of aggression: an observational study of father–child play dyads

Abstract: Rough-and-tumble play (RTP) is a common form of play between fathers and children. It has been suggested that RTP can contribute to the development of selfregulation. This study addressed the hypothesis that the frequency of father-child RTP is related to the frequency of physically aggressive behavior in early childhood. This relationship was expected to be moderated by the dominance relationship between father and son during play. Eighty-five children between the ages of 2 and 6 years were videotaped during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 57 publications
2
97
0
4
Order By: Relevance
“…In this way, the child's later preferences and play choices are gradually formed and are seen in the kindergarten (Carlson, 2011;Flanders et al, 2009;Stevenson, 2014). Thus, under the impact of the "gender habitus", boys prefer RTP to a greater extent than the girls and, indeed, they choose competitive power plays, whereas girls choose lighter forms of RTP (Pellegrini & Smith, 1998;Storli, 2013).…”
Section: International Research In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the child's later preferences and play choices are gradually formed and are seen in the kindergarten (Carlson, 2011;Flanders et al, 2009;Stevenson, 2014). Thus, under the impact of the "gender habitus", boys prefer RTP to a greater extent than the girls and, indeed, they choose competitive power plays, whereas girls choose lighter forms of RTP (Pellegrini & Smith, 1998;Storli, 2013).…”
Section: International Research In Educationmentioning
confidence: 99%
“…In these studies, the participation of gender in RTP is examined (see : Boulton, 1996;Jarvis, 2004;Storli, 2013), or there is an approach concerning the teachers' or parents' perceptions on RTP (see : Coplan, Bullock, Archbell, & Bosacki, 2015;Di Carlo, Baumgartner, Ota, & Jenkins, 2015;Fletcher, May, St George, Morgan, & Lubans, 2011;Tannock, 2008). There is also observation research on RTP developing among father and son and, consequently, apprehension of the impact on the boys' behavior forming and plays at school (see : Flanders, Leo, Paquette, Pihl, & Séguin, 2009;McBride-Chang & Nagy Jacklin, 1993). The research to be presented is the first carried out in Greece and there is an attempt to contribute to academic literature, offering a picture of how gender affects RTP choice in kindergarten.…”
Section: Introductionmentioning
confidence: 99%
“…Flanders et al (2009) and Tannock (2011) found from their observations of children playing that boys and girls engaged in RTP with similar frequencies. However, Colwell and Lindsey (2005) found that boys engaged in RTP more frequently than girls.…”
Section: Gender Differences In Frequency Of Rtpmentioning
confidence: 99%
“…In comparison, emotional regulation in girls was positively associated with fantasy and sociodramatic play. Flanders et al (2009) conducted a study in Canada to understand the fatherchild play relationship and regulation of children's aggressive behavior based on observations that "fathers tend to stimulate their children physically, emotionally, and cognitively during play" (p. 286). A sample of 85 father-child dyads participated in the study, with an almost equal number of boys (n = 43) and girls (n = 42) who ranged in age from 2 through 6 years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation